1997
DOI: 10.1074/jbc.272.16.10353
|View full text |Cite
|
Sign up to set email alerts
|

Function of the Escherichia coli msbB Gene, a Multicopy Suppressor of htrB Knockouts, in the Acylation of Lipid A

Abstract: Overexpression of the

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
256
0

Year Published

1998
1998
2022
2022

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 198 publications
(261 citation statements)
references
References 31 publications
5
256
0
Order By: Relevance
“…The msbB gene of Salmonellae is responsible for the terminal myristoylation of lipid A. 43,44 Disruption of the msbB gene in Salmonellae results in stable mutants that lower TNF induction. Introducing msbB2 mutations into Salmonella strain YS72 (hyperinvasive, purI2, xyl2), previously used for tumor targeting, has demonstrated that introduction of these mutations does not interfere with the ability of the Salmonellae to target tumors.…”
Section: Discussionmentioning
confidence: 99%
“…The msbB gene of Salmonellae is responsible for the terminal myristoylation of lipid A. 43,44 Disruption of the msbB gene in Salmonellae results in stable mutants that lower TNF induction. Introducing msbB2 mutations into Salmonella strain YS72 (hyperinvasive, purI2, xyl2), previously used for tumor targeting, has demonstrated that introduction of these mutations does not interfere with the ability of the Salmonellae to target tumors.…”
Section: Discussionmentioning
confidence: 99%
“…Important enzymes of Kdo metabolism are CMP-Kdo synthetase (CKS), determined by the kdsB gene [4][5][6], and Kdo transferase, determined by the kdtA gene [7,8]. CKS catalyzes the activation of Kdo according to: CTP + Kdo M-~g~+CMP-Kdo + PPi, whereas Kdo transferase participates in the synthesis of the lipid A moiety of lipopolysaccharide.…”
Section: Introduction 2 Materials and Methodsmentioning
confidence: 99%
“…Growth of 32 P i -Labeled Cells-Cells were grown and labeled using the methods described previously (19,29). In general, labeling of the glycerophospholipids and lipid A was achieved by dilution of overnight cultures with 125 ml of pre-warmed fresh LB broth containing appropriate antibiotics to yield A 550 ϭ 0.05.…”
Section: Figmentioning
confidence: 99%
“…Two multicopy suppressors of htrB mutations (designated msbA and msbB) were also reported (20,21). The msbB gene displays sequence homology to htrB (20,22) and encodes a distinct acyltransferase (16,19) (Fig. 2) that can substitute for htrB at 42°C, when overexpressed on high copy plasmids.…”
mentioning
confidence: 99%
See 1 more Smart Citation